Electrophotographic member, fixing device, and electrophotographic image forming apparatus
The electrophotographic member with a base, elastic, and surface layer structure, featuring controlled crystallinity and spherulite size in the surface layer, addresses the balance of abrasion resistance, flexibility, and image glossiness, ensuring stable high-quality image formation.
Patent Information
- Application Number
- JP2023104692
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2025-01-16
AI Technical Summary
Existing electrophotographic fixing members face challenges in achieving a balance between abrasion resistance, flexibility to follow paper irregularities, and maintaining high image glossiness due to issues with surface layer smoothness and molecular rigidity, particularly when using tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers like 451HP-J.
The electrophotographic member is designed with a base layer, an elastic layer, and a surface layer, where the surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer with controlled crystallinity and spherulite size, ensuring an endothermic peak temperature of 304°C or less, heat absorption of 21 J/g or more, and an area average spherulite diameter of 40 μm or less, enhancing abrasion resistance and image glossiness.
This configuration improves the member's ability to withstand paper abrasion, maintain flexibility, and produce high-quality images with enhanced glossiness by controlling the crystallinity and spherulite size of the surface layer, thereby stabilizing the formation of high-quality electrophotographic images.
Smart Images

Figure 2025004836000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic member used in a fixing device of an electrophotographic image forming apparatus, and to a fixing device and an electrophotographic image forming apparatus including the electrophotographic member. [Background technology]
[0002] Electrophotographic members, such as fixing members used in fixing devices of electrophotographic image forming apparatuses such as printers, copiers, and facsimiles, are available in the form of a film or roller. Known fixing members include, for example, a film- or roller-shaped base material made of heat-resistant resin or metal, on which an elastic layer or a surface layer made of heat-resistant rubber or the like is formed as necessary. For example, a fluororesin having releasability is used for the surface layer.
[0003] The elastic layer functions as a layer that provides flexibility to the fixing member in order to ensure a fixing nip in the fixing device and to allow the surface of the fixing member to follow the unevenness of the paper. In addition, the surface layer is preferably made of tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA) as a fluororesin that has excellent releasability to toner. In recent years, there has been a demand for a longer life of the fixing member from the viewpoint of reducing running costs and saving energy. In particular, the surface layer of the fixing member is easily worn by the edge of the paper, which has a significant impact on the life of the fixing member.
[0004] Patent Document 1 proposes a technique in which a core bar is coated with PFA, then heated to a temperature equal to or higher than the melting point of the PFA, and then slowly cooled to increase the crystallinity of the PFA and improve wear resistance. Moreover, Patent Document 2 proposes obtaining high surface smoothness by using a fluororesin having small spherulite size as a surface layer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-093650 A [Patent Document 2] JP 2000-010430 A Summary of the Invention [Problem to be solved by the invention]
[0006] As in Patent Document 1, the fixing member is heated above the melting point of the PFA, which is the surface layer, and then slowly cooled to increase the crystallinity of the PFA and improve the abrasion resistance of the paper. However, according to the study by the present inventors, when the PFA is slowly cooled, the crystal growth rate increases relative to the frequency of spherulite nuclei generation, and large spherulites may form on the surface of the surface layer. This causes large irregularities along the spherulite shape, and the surface smoothness of the fixing member decreases. This causes the irregularities on the surface of the surface layer to be transferred to the image surface, resulting in a problem of reduced image gloss.
[0007] Therefore, as in Patent Document 2, a fixing member having high surface smoothness can be obtained by using a fluororesin with small spherulite size, such as 451HP-J (product name: manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd.) as the surface layer. However, when a PFA with a high melting point such as 451HP-J is used, the flexibility of the surface layer decreases due to the high molecular rigidity. Therefore, even if the fixing member is given flexibility by the elastic layer, the ability to follow the unevenness of the paper may be insufficient, and image quality may be impaired. Therefore, the present inventors have recognized that there is a problem in satisfying all of the abrasion resistance to paper, image glossiness, and ability to follow the unevenness of the paper.
[0008] At least one aspect of the present disclosure is directed to providing an electrophotographic member that contributes to the stable formation of high-quality electrophotographic images. At least one aspect of the present disclosure is directed to providing a fixing device that contributes to the stable formation of high-quality electrophotographic images. Furthermore, at least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images. [Means for solving the problem]
[0009] According to at least one aspect of the present disclosure, there is provided an electrophotographic member having at least a base layer, an elastic layer, and a surface layer, in that order, comprising: the surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, The sample sampled from the surface layer was used as a measurement sample, and measurements were carried out twice using a differential scanning calorimeter (DSC) at a heating rate and a cooling rate of 20° C. / min. The endothermic curves obtained were as follows: The endothermic peak temperature in the second heating process is 304°C or less, The amount of heat absorbed during the first heating process is 21 J / g or more, An electrophotographic member is provided in which D3 is an area average diameter of the spherulites on the outer surface of the surface layer, and D3 is 40 μm or less.
[0010] According to at least one aspect of the present disclosure, there is provided a fixing device in an electrophotographic image forming apparatus, comprising: The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, A fixing apparatus is provided, wherein at least one of the fixing member and the pressure member is the electrophotographic member described above.
[0011] According to at least one aspect of the present disclosure, an electrophotographic member contributing to the stable formation of a high-quality electrophotographic image can be obtained. Also, according to at least one aspect of the present disclosure, a fixing device contributing to the stable formation of a high-quality electrophotographic image can be obtained. Furthermore, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming a high-quality electrophotographic image can be obtained. Effect of the Invention
[0012] According to at least one aspect of the present disclosure, it is possible to provide an electrophotographic member that has a high paper conformability while improving the abrasion resistance of the surface layer against paper, and that can provide good image quality with high image gloss. Also, according to at least one aspect of the present disclosure, it is possible to provide a fixing device that has a high paper conformability while improving the abrasion resistance of the surface layer against paper, and that can provide good image quality with high image gloss, and an electrophotographic image forming apparatus equipped with the fixing device. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram of an electrophotographic image forming apparatus according to one embodiment of the present disclosure. [Diagram 2] 1 is a schematic diagram of a fixing device according to an embodiment of the present disclosure; FIG. [Diagram 3] FIG. 1 is a schematic diagram of a fixing film according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In this specification, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower limit and the upper limit, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined. Hereinafter, the embodiment of the present disclosure will be described in detail. Note that the technical scope of the present disclosure is not limited to the following description.
[0015] An electrophotographic member according to at least one embodiment of the present disclosure has at least a base layer, an elastic layer, and a surface layer in this order, the surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, The sample sampled from the surface layer was used as a measurement sample, and measurements were carried out twice using a differential scanning calorimeter (DSC) at a heating rate and a cooling rate of 20° C. / min. The endothermic curves obtained were as follows: The endothermic peak temperature in the second heating process is 304°C or less, The amount of heat absorbed during the first heating process is 21 J / g or more, When the area average diameter of the spherulites on the outer surface of the surface layer is designated as D3, D3 is 40 μm or less.
[0016] <Electrophotographic materials> The electrophotographic member according to at least one embodiment of the present disclosure is, for example, a fixing member. For example, the electrophotographic member is a fixing belt. The electrophotographic member may also be an electrophotographic belt having an endless shape. The electrophotographic member has at least a base layer, an elastic layer, and a surface layer in this order. That is, the electrophotographic member has a base layer, an elastic layer on the base layer, and a surface layer on the elastic layer. Other layers may be provided between the base layer, the elastic layer, and the surface layer, and on the inner peripheral side of the base layer and the outer peripheral side of the surface layer, as necessary.
[0017] The fixing member 41 is, for example, a fixing film 41, as shown in Figs. 2 and 3. The fixing member 41 has a base layer 41b, an elastic layer 41c, and a surface layer 41a. The surface layer 41a can be a release layer having releasability for toner, for example. The surface layer 41a can form the outer surface of the electrophotographic member. The surface layer 41a may be adhered to the surface of the elastic layer 41c by an adhesive layer (not shown). The inner peripheral surface side of the base layer 41b may be provided with an inner sliding layer (not shown).
[0018] Each layer will be specifically described below. <base layer> The material of the base layer 41b is not particularly limited and may be any known electrophotographic material. For example, metals and alloys such as aluminum, iron, stainless steel (SUS), and nickel, as well as heat-resistant resins such as polyimide, are used. Stainless steel is preferred. The thickness of the base layer 41b is not particularly limited, but is preferably 20 μm to 100 μm, more preferably 20 μm to 50 μm, from the viewpoints of strength, flexibility, and heat capacity.
[0019] The outer surface of the base layer 41b may be subjected to a surface treatment to impart adhesion to the elastic layer 41c. The surface treatment may be one or a combination of a physical treatment such as blasting, lapping, or polishing, or a chemical treatment such as oxidation, coupling agent treatment, or primer treatment.
[0020] When the elastic layer 41c containing silicone rubber is provided on the surface of the base layer 41b, it is preferable to perform a primer treatment on the surface of the base layer 41b in order to improve the adhesion between the base layer 41b and the elastic layer 41c. Examples of the primer used in the primer treatment include paints in which a silane coupling agent, a silicone polymer, hydrogenated methylsiloxane, an alkoxysilane, a reaction accelerating catalyst, and a coloring agent such as red iron oxide are appropriately mixed and dispersed in an organic solvent.
[0021] The primer can be appropriately selected depending on the material of the base layer 41b, the type of the elastic layer 41c, or the form of the crosslinking reaction. A primer containing a hydrosilyl group is preferably used to impart adhesiveness by reaction with an aliphatic group. When the elastic layer 41c contains a large amount of hydrosilyl groups, a primer containing an unsaturated aliphatic group is preferably used.
[0022] Other examples of the primer include those containing an alkoxy group. A commercially available primer can be used. The primer treatment includes a step of applying the primer to the outer surface of the base layer 41b (the surface to be bonded to the elastic layer 41c) and drying or baking the primer.
[0023] <Inner surface sliding layer> The inner circumferential surface side of the base layer 41b may be provided with an inner sliding layer. A resin having both high durability and high heat resistance, such as polyimide resin, is suitable for the inner sliding layer. Since the inner sliding layer is gradually worn away by friction, it is preferable to provide a thickness that allows it to function as a sliding layer throughout the duration of use. On the other hand, a thickness that does not interfere with the supply of heat from the heater is preferable. Therefore, the thickness is preferably 5 to 20 μm, more preferably 10 to 15 μm. The inner sliding layer may be formed using a known coating method or the like.
[0024] <Elastic layer> The elastic layer 41c may be made of any known electrophotographic material, and is not particularly limited. The elastic layer 41c preferably contains silicone rubber, which has excellent heat resistance. As the raw material for the silicone rubber, addition-curing liquid silicone rubber is preferably used. The elastic layer 41c may be formed, for example, by applying addition-curing liquid silicone rubber to the outer surface of the base layer 41b and then heating and curing the rubber. The application method is not particularly limited, and any known method may be used.
[0025] The thickness of the elastic layer 41c can be appropriately designed taking into consideration the surface hardness of the fixing member and the width of the fixing nip portion to be formed, and is preferably 100 μm to 500 μm, more preferably 200 μm to 400 μm.
[0026] As the silicone rubber, for example, a cured product of an addition curing type liquid silicone rubber mixture described later can be used. The elastic layer 41c can be formed by applying and heating the liquid silicone rubber mixture by a known method.
[0027] The liquid silicone rubber mixture typically contains the following components (a) to (d): Component (a): an organopolysiloxane having an unsaturated aliphatic group; Component (b): an organopolysiloxane having active hydrogen bonded to silicon; Component (c): catalyst; Component (d): Thermally conductive filler Each component will be described below.
[0028] Component (a) The organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group, and examples thereof include those represented by the following formulas (1) and (2). The organopolysiloxane having an unsaturated aliphatic group is preferably a linear type. [ka]
[0029] In formula (1), m 1 is an integer equal to or greater than 0, and n 1 represents an integer of 3 or more. In addition, in the structural formula (1), R 1 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 1 At least one of R represents a methyl group. 2 each independently represents an unsaturated aliphatic group. [ka]
[0030] In formula (2), n 2 denotes a positive integer, and R 3 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 3 At least one of R represents a methyl group. 4 each independently represents an unsaturated aliphatic group.
[0031] In formulas (1) and (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by include the following groups. Unsubstituted hydrocarbon groups Alkyl groups (eg, methyl, ethyl, propyl, butyl, pentyl, hexyl). Aryl groups (eg, phenyl groups). Substituted hydrocarbon groups Substituted alkyl groups (eg, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, 3-methoxypropyl).
[0032] The organopolysiloxanes represented by formulas (1) and (2) have at least one methyl group directly bonded to the silicon atom forming the chain structure. However, for ease of synthesis and handling, R 1 and R 3 It is preferable that 50% or more of each group are methyl groups, and all of R 1 and R 3 More preferably, is a methyl group.
[0033] In addition, in formulas (1) and (2), R 2 and R 4 Examples of the unsaturated aliphatic group that can be represented by include the following groups. That is, examples of the unsaturated aliphatic group include a vinyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, and a 5-hexenyl group. Among these groups, R 2 and R 4 is preferably a vinyl group.
[0034] From the viewpoint of moldability, the viscosity of component (a) is 1000mm 2 / s or more 50000mm 2 / s or less is preferable. 2 / s or lower, elastic layer 20c is required It becomes difficult to adjust the hardness to 50,000 mm. 2 If the viscosity is higher than 1 / s, the mixture will become too viscous and coating will become difficult. Viscosity (kinetic viscosity) can be measured using a capillary viscometer or rotational viscometer in accordance with JIS Z 8803:2011.
[0035] The blending amount of component (a) is preferably 55% by volume or more from the viewpoint of durability and 65% by volume or less from the viewpoint of heat conductivity, based on the liquid silicone rubber mixture used to form the elastic layer 20c.
[0036] Ingredient (b) The organopolysiloxane having active silicon-bonded hydrogens functions as a crosslinker that reacts with the unsaturated aliphatic groups of component (a) in the presence of a catalyst to form a cured silicone rubber. Any organopolysiloxane having a Si-H bond can be used as component (b). In particular, from the viewpoint of reactivity with the unsaturated aliphatic group of component (a), it is preferable to use one having an average of 3 or more hydrogen atoms bonded to silicon atoms in one molecule.
[0037] Specific examples of component (b) include the linear organopolysiloxane shown in the following formula (3) and the cyclic organopolysiloxane shown in the following formula (4). [ka]
[0038] In formula (3), m 2 is an integer equal to or greater than 0, and n 3 indicates an integer of 3 or more, and R 5 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group. [ka]
[0039] In formula (4), m 3 is an integer equal to or greater than 0, and n 4 indicates an integer of 3 or more, and R 6 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group.
[0040] R in formulas (3) and (4) 5 and R 6Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by R 1 Among these, R 5 and R 6 It is preferable that 50% or more of each group are methyl groups, and all of R 5 and R 6 More preferably, is a methyl group.
[0041] Ingredient (c) The catalyst used in forming the silicone rubber may be, for example, a hydrosilylation catalyst for promoting the curing reaction. As the hydrosilylation catalyst, for example, a known substance such as a platinum compound or a rhodium compound may be used. The amount of the catalyst to be added may be appropriately set and is not particularly limited.
[0042] Ingredient (d) The elastic layer 41c may contain a filler. The filler is added to control the thermal conductivity, heat resistance, and elastic modulus. Examples of the thermally conductive filler include metals, metal compounds, and carbon fibers. Highly thermally conductive fillers are more preferable, and specific examples thereof include the following materials. Silicon metal (Si), silicon carbide (SiC), silicon nitride (Si 3 N 4 ), boron nitride (BN), aluminum nitride (AlN), alumina (Al 2 O 3 ), iron oxide (Fe 2 O 3 ), zinc oxide (ZnO), magnesium oxide (MgO), titanium oxide (TiO 2 ), silica (SiO 2 ), copper (Cu), aluminum (Al), silver (Ag), iron (Fe), nickel (Ni), carbon black (C), carbon nanotubes (C), vapor grown carbon fiber, PAN (polyacrylonitrile) carbon fiber, pitch-based carbon fiber.
[0043] <Adhesive layer> An adhesive layer may be provided between the elastic layer 41c and the surface layer 41a to bond them together. The material of the adhesive layer is not particularly limited, and any known material may be used. The adhesive layer preferably contains a silicone rubber adhesive. The thickness of the adhesive layer is not particularly limited, but is preferably 1 to 20 μm, and more preferably 3 to 10 μm.
[0044] <Surface layer> The surface layer 41a contains a tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA). The surface layer 41a is preferably made of PFA. A sample taken from the surface layer 41a is used as a measurement sample, and measurements are performed twice using a differential scanning calorimeter (DSC) with a heating rate and a cooling rate of 20°C / min. In the endothermic curve at this time, the endothermic peak temperature in the second heating process is 304°C or lower, and the amount of endotherm in the first heating process is 21 J / g or higher. The surface layer has an area-average diameter D3 of spherulites on the outer surface thereof, and D3 is 40 μm or less. The reason why an electrophotographic member having such a surface layer can satisfy all of the abrasion resistance against paper, the image glossiness, and the ability to follow the unevenness of paper will be described below together with the description of each configuration of the surface layer.
[0045] PFA is a copolymer of perfluoroalkylvinylether (PAVE) and tetrafluoroethylene (TFE). The surface layer 41a containing PFA can be formed by applying a dispersion (water-based dispersion paint) or powder paint mainly composed of PFA to the surface of the elastic layer 41c, and then heating the coating to a temperature above the melting point to form a film. Alternatively, a PFA tube manufactured by extrusion molding can be applied to the surface of the elastic layer 41c. The surface layer 41a can be, for example, a PFA tube.
[0046] The endothermic peak in the second heating process in the DSC measurement is an endothermic peak due to the crystal melting of PFA, and means the melting point of PFA. The melting point of PFA is correlated with the rigidity of the molecular chain, and the higher the rigidity of the molecular chain, the higher the melting point of PFA. The rigidity of the molecular chain of PFA can be controlled by adjusting the ratio of PAVE to TFE. For example, by using perfluoropropyl vinyl ether as PAVE and setting the copolymerization ratio (molar ratio) of PAVE and TFE (PAVE / TFE) to the preferred range described below, it is easy to control the melting point to 304°C or less. From the viewpoint of controlling the melting point, for example, it is more preferable to bring the copolymerization ratio (molar ratio) (PAVE / TFE) closer to 2.0 / 98.0.
[0047] If the endothermic peak temperature (melting point) in the second heating process exceeds 304°C, the molecular chains will be highly rigid, resulting in low flexibility as a surface layer and impaired ability to conform to the unevenness of the paper. By keeping the endothermic peak temperature in the second heating process at 304°C or less, it is believed that the flexibility will be good and the layer will be able to conform to the unevenness of the paper, resulting in a fixed image with reduced toner melting unevenness.
[0048] The PFA is not particularly limited, and known PFAs can be used. The copolymerization ratio (molar ratio) (PAVE / TFE) of perfluoroalkyl vinyl ether (PAVE) and tetrafluoroethylene (TFE) is preferably 1.5 / 98.5 to 4.5 / 95.5, more preferably 1.5 / 98.5 to 4.0 / 96.0. Commercially available PFAs may be used. Specific examples include AP-230 (trade name, manufactured by Daikin Industries, Ltd.) and AP-231SH (trade name, manufactured by Daikin Industries, Ltd.), which is a PFA with a fully fluorinated end group.
[0049] The PFA can be confirmed by, for example, the presence of a peak characteristic of polytetrafluoroethylene (PTFE) in the ATR spectrum of FT-IR, and the presence of a peak at 994 cm -1 This can be confirmed by checking for the presence of a small peak nearby. First, the characteristic peak of PTFE is 1200 cm -1 (CF 2 Inverse symmetric expansion and contraction), 1150cm -1 (CF 2 Symmetrical expansion and contraction), 640cm -1 (CF 2 Out-of-plane bending angle (wagging), 555 cm -1 (CF 2 In-plane deflection angle (scissors), 505 cm -1 (CF 2 In addition, there is a characteristic of PFA, 994cm -1 The position of the peak at around 994 cm varies depending on the length of the carbon chain of the perfluoroalkyl vinyl ether moiety. -1 In the case of the perfluoroethoxy group, it appears at 1090 cm -1 In the case of the perfluoromethoxy group, it appears at 881 cm -1 Appears in.
[0050] The amount of heat absorbed during the first heating process in the DSC measurement is the amount of heat absorbed due to the crystalline melting of PFA. The crystallinity of PFA can be calculated by dividing the amount of heat absorbed by the heat of complete crystalline melting of PFA (92.9 J / g). When the amount of heat absorbed is 21 J / g or more, the PFA in the surface layer has a degree of crystallinity, which results in good abrasion resistance to paper.
[0051] The amount of heat absorbed during the first temperature rise is preferably 27 J / g or less. If the amount of heat absorbed is 27 J / g or less, the ability to conform to the unevenness of the paper is improved. The amount of heat absorbed during the first temperature rise is preferably 21 to 27 J / g, more preferably 22 to 27 J / g, and even more preferably 25 to 27 J / g. In addition, unless otherwise specified, DSC measurements in this disclosure are in accordance with Japanese Industrial Standards (JIS) K7121-2012.
[0052] One method for achieving a heat absorption of 21 J / g or more is to heat the surface layer 41a to a temperature above the melting point of PFA after formation during the manufacturing process of the fixing member, and then promote crystallization of the PFA by controlling the cooling rate. Although the specific method is not particularly limited, the following methods for heat treatment of the surface layer can be used.
[0053] After the surface layer is formed, an upright cylindrical heating cylinder capable of heating up to, for example, 330° C. or higher is used to heat the entire electrophotographic member. A band heater equipped with a thermocouple is installed inside the heating cylinder to control the heating temperature of the fixing member. The heating temperature is preferably from the melting point of PFA to 350° C. The heating time is determined so that the temperature of the surface layer can sufficiently reach the desired temperature. The heating time may be any temperature within the range of 1 to 20 minutes, 1 to 10 minutes, or 2 to 5 minutes, for example.
[0054] After the heating is completed, the cooling rate of the heating cylinder is controlled to control the cooling rate of the fixing member. For example, the cooling rate can be controlled by providing an air supply nozzle on the outer periphery of the heating cylinder and adjusting the air flow rate. The slower the cooling rate in the crystallization temperature range of PFA, the more the crystallization of PFA can be promoted, and it is preferable to adjust the cooling rate so that the heat absorption amount is 21 J / g or more. It is preferable to control the cooling rate until the temperature of the surface layer falls below the crystallization temperature range of PFA. The cooling rate may be in a range that can be controlled to an endothermic amount of 21 J / g or more, and is not particularly limited, but is preferably 5 to 60°C / min, and more preferably 10 to 30°C / min.
[0055] Furthermore, if the endothermic peak temperature in the second heating process is 297°C or higher, the rigidity of the PFA molecules becomes moderately high, and the amount of heat absorbed in the first heating process can be easily increased to 21 J / g or higher by controlling the cooling rate. For this reason, the endothermic peak temperature in the second heating process is preferably 297°C or higher, and more preferably 300°C or higher. The endothermic peak temperature in the second temperature increase process is preferably from 297 to 304°C, more preferably from 300 to 304°C, and further preferably from 300 to 302°C.
[0056] When the area average diameter of the spherulites on the outer surface of the surface layer 41a is D3, D3 is 40 μm or less. When D3 is 40 μm or less, the surface smoothness is good, and a fixed image with high image glossiness can be obtained. The smaller D3 is, the better the surface smoothness is. On the other hand, from the viewpoint of reducing the amorphous part of PFA present in the gaps of the lamellar structure of the spherulites, suppressing the decrease in crystallinity, and further improving the wear resistance, D3 is preferably 5 μm or more. The outer surface of the surface layer refers to the surface that forms the outer surface of the electrophotographic member.
[0057] D3 is preferably 5 to 40 μm, more preferably 10 to 35 μm, and even more preferably 20 to 34 μm. It is believed that the value of D3 can be reduced by increasing the frequency of spherulite nuclei generation relative to the crystal growth rate of PFA, for example, by placing a substance that acts as a nucleating agent for spherulites on the inner side of the surface layer 41a, i.e., in the vicinity of the surface facing the elastic layer. This increases the frequency of spherulite nuclei generation on the inner side.
[0058] In the process of cooling the molten PFA, spherulites grow from the spherulite nuclei, and the crystal growth stops when the PFA comes into contact with other spherulites. Therefore, if the frequency of spherulite nuclei is high, the diameter of the spherulites formed on the inner side of the surface layer becomes smaller. In the surface layer 41a, the smaller the diameter of the spherulites formed on the inner side, the smaller the diameter of the spherulites on the outer surface. This is considered to be because spherulites are first formed on the inner side, and then molecules are attached to the surface, and crystallization proceeds toward the outer surface. Therefore, if the frequency of spherulite nuclei is high on the inner side, D3 tends to be small, and D3 tends to be 40 μm or less.
[0059] In order to make the nucleating agent exist on the inner surface side of the surface layer, for example, a method is used in which a PFA tube is used to prepare the surface layer 41a, and the inner surface is irradiated with excimer laser light under controlled irradiation conditions. In the excimer laser treatment, fluorine atoms on the inner surface of the PFA tube are released, and reactions such as carbonization and the generation of carbonyl groups by reaction with oxygen occur. As a result, the element ratio on the inner surface changes. The carbon generated by this becomes the nucleating agent, so this method can make the nucleating agent exist on the inner surface side.
[0060] As described above, for the surface layer containing PFA, the endothermic peak temperature in the second heating process is set to 304°C or less, the endothermic amount in the first heating process is set to 21 J / g or more, and D3 is set to 1. By setting the thickness to 40 μm or less, it is possible to satisfy all of the requirements for abrasion resistance to paper, image glossiness, and ability to conform to unevenness of paper.
[0061] In the present disclosure, when the carbon element ratio on the surface of the surface layer facing the elastic layer is C atomic %, the fluorine element ratio is F atomic %, and the oxygen element ratio is O atomic %, CF / 2-O≧30 It is preferable to satisfy the following:
[0062] By being in the above range, the surface of the surface layer facing the elastic layer becomes rich in carbon, and the surface smoothness can be improved. This is because the carbon acts as a nucleating agent for spherulites, and the frequency of spherulite nuclei occurring on the inner side of the surface layer increases, so D3 becomes smaller for the above-mentioned reason, and the surface smoothness is improved. CF / 2-O is preferably 30-50, and more preferably 32-40.
[0063] The thickness of the surface layer 41a is preferably 30 μm or less. If the thickness is 30 μm or less, the effect of the nucleating agent on the inner surface side of the surface layer on D3 becomes larger, and the surface smoothness can be improved. The thickness of the surface layer is more preferably 10 to 30 μm, and further preferably 15 to 30 μm.
[0064] As a specific method for achieving the above range, the following method can be used. Here, an example is given in which a PFA tube is used to prepare the surface layer 41a, but the surface layer according to the present disclosure is not limited to being formed using a PFA tube.
[0065] The PFA tube can be produced, for example, by extruding molten PFA from a cylindrical die. Such a PFA tube is quenched during the extrusion process and crystallization proceeds rapidly, so the crystals are oriented in the extrusion direction and the crystallinity is low. After the PFA tube is coated on the surface of the elastic layer 41c to form the surface layer 41a, the surface layer is heated to increase the crystallinity and form spherulites on the surface of the surface layer. Increasing the crystallinity makes it easier to control the amount of heat absorption during the first heating process to within the above-mentioned range.
[0066] The inner surface of the PFA tube can be previously treated with sodium, excimer laser, ammonia, or the like to improve wettability and adhesion to the elastic layer 41c or an adhesive layer that is provided as needed. It is preferable to treat the inner surface of the PFA tube using excimer laser treatment.
[0067] For the excimer laser treatment, it is preferable to attach a compound that absorbs ultraviolet light to the inner surface of the PFA tube, and then irradiate the inner surface with ultraviolet laser light such as KrF excimer laser light or ArF excimer laser light. Known compounds that absorb ultraviolet light can be used. For example, an aqueous solution is prepared by mixing a compound that absorbs ultraviolet light such as sodium benzoate with a known fluorine-based surfactant, and the aqueous solution is applied to the inner surface of the PFA tube and allowed to dry naturally.
[0068] In the excimer laser treatment, fluorine atoms on the inner surface of the PFA tube are released, and reactions such as carbonization and the generation of carbonyl groups through reactions with oxygen occur. As a result, the element ratio on the surface layer facing the elastic layer changes, making it easier to control CF / 2-O within the above-mentioned range.
[0069] In the present disclosure, the irradiation conditions of the excimer laser light are controlled to advance the carbonization of the inner surface of the PFA tube, thereby changing the element ratio of the surface layer on the side facing the elastic layer to within the above-mentioned range. The irradiation conditions of the excimer laser beam are usually selected from the viewpoint of improving wettability and adhesiveness, and the dose per shot or the number of shots is adjusted. In the present disclosure, it is preferable to increase the number of shots more than is usually necessary to sufficiently advance carbonization of the inner surface of the PFA tube. For example, the dose of the excimer laser beam is preferably 100 to 600 mJ / cm. 2 / pulse, more preferably 200-400mJ / cm 2 The number of shots is preferably 3 to 10, and more preferably 6 to 8.
[0070] In addition, when the number-average diameter of the spherulites on the outer surface of the surface layer 41a is D1, it is preferable that D3 / D1 is 1.5 or less. The closer the value of D3 / D1 is to 1, the narrower and more uniform the distribution of the equivalent circle diameters of the spherulites is. By having D3 / D1 be 1.5 or less, the surface smoothness is improved, and a fixed image with higher image gloss can be obtained.
[0071] The value of D3 / D1 can be reduced by slowing down the cooling rate in the crystallization temperature range of PFA in the heat treatment of the surface layer described above. D3 / D1 is preferably, for example, 1.0 to 1.5. D1 is preferably 4 to 35 μm, and more preferably 10 to 35 μm.
[0072] Moreover, the arithmetic mean roughness Ra of the outer surface of the surface layer 41a is preferably 0.20 μm or less. By having Ra of 0.20 μm or less, the surface smoothness is improved, and a fixed image with high image gloss can be obtained. By having the area mean diameter D3 of 40 μm or less, it becomes easier to make Ra 0.20 μm or less. Ra is more preferably 0.05 to 0.20 μm, and further preferably 0.10 to 0.18 μm.
[0073] The means for covering the surface of the elastic layer with the PFA tube is not particularly limited, and known means can be used. For example, a method of expanding and covering the fluororesin tube from the outside (expansion covering method) can be used. A vacuum expansion covering method in which the PFA tube is vacuum expanded and covered from the outside can be used.
[0074] <Electrophotographic image forming apparatus> 1 is a cross-sectional view of a color electrophotographic printer, which is an example of an electrophotographic image forming apparatus (hereinafter also referred to as an "image forming apparatus") according to the present embodiment, taken along the conveying direction of a recording material. In this embodiment, the color electrophotographic printer is simply referred to as a "printer."
[0075] The printer 1 shown in FIG. 1 includes image forming units 10 for the colors Y (yellow), M (magenta), C (cyan), and Bk (black). A photosensitive drum (photoconductor) 11 is pre-charged by a charger 12. The photosensitive drum 11 is then exposed by a laser scanner 13 to form an electrostatic latent image. The electrostatic latent image is turned into a toner image by a developer 14. The toner images on the photosensitive drum 11 are sequentially transferred by a primary transfer blade 17 to an image carrier, for example, an intermediate transfer belt 31. After transfer, the toner remaining on the photosensitive drum 11 is removed by a cleaner 15. As a result, the surface of the photosensitive drum 11 becomes clean and is prepared for the next image formation.
[0076] Meanwhile, recording material P is sent out one by one from paper feed cassette 20 or multi-paper feed tray 25 in the direction of arrow 3 and fed into registration roller pair 23. Registration roller pair 23 temporarily receives recording material P and straightens it out if it is skewed. Then, registration roller pair 23 synchronizes with the toner image on intermediate transfer belt 31 and sends recording material P between intermediate transfer belt 31 and secondary transfer roller 35. The color toner image on the intermediate transfer belt is transferred onto recording material P by a transfer body such as secondary transfer roller 35. Thereafter, the toner image on recording material P is fixed to recording material P by heating and pressurizing recording material P by fixing device 40. The toner image is fixed onto the recording material.
[0077] The electrophotographic image forming apparatus includes a fixing device 40. Next, the fixing device in the electrophotographic image forming apparatus will be described. The fixing device includes a fixing member and a pressure member disposed opposite the fixing member. FIG. 2 is a schematic diagram of the fixing device 40, and is an example of a film heating type heating device (tensionless type). This type of heating device is used in this embodiment, but a roller pair type or film type heating device can also be used.
[0078] Reference numeral 43 denotes a ceramic heater (hereafter referred to as heater) as a heating element. The heater 43 is basically composed of a long, thin ceramic substrate with its longitudinal direction perpendicular to the drawing, and an energized heat generating resistor layer provided on the surface of the substrate. The heater 43 is a low-heat capacity heater that increases in temperature with a steep rise characteristic overall when electricity is applied to the heat generating resistor layer. It is also configured to switch the energized area depending on the longitudinal width size of the recording material.
[0079] An electrophotographic member according to at least one embodiment of the present disclosure can be used as, for example, a fixing member. The fixing film 41 is a cylindrical (endless) heat-resistant fixing member serving as a heating member for transmitting heat, and is loosely fitted on a support member (heater holder) including the heater 43. The structure of the fixing film 41 is as shown in FIG. 3, and is a fixing film having a three-layer composite structure including at least a surface layer 41a, an elastic layer 41c, and a base layer 41b.
[0080] The pressure roller 44 is a heat-resistant elastic pressure roller as a pressure member, and has a core metal and an elastic layer made of heat-resistant rubber such as silicone rubber or fluororubber, or a silicone rubber foam. Both ends of the core metal are rotatably supported by bearings. The electrophotographic member according to at least one embodiment of the present disclosure can also be used as a pressure member, for example. That is, it is preferable that at least one of the fixing member and the pressure member is the electrophotographic member. For example, the pressure member can be configured similarly to the fixing film 41, and the pressure member can have a three-layer composite structure including a surface layer 41a, an elastic layer 41c, and a base layer 41b.
[0081] The fixing film 41 and heater 43 are arranged above the pressure roller 44 in parallel to the pressure roller 44, and pressed by a pressing member (not shown). In this manner, the lower surface of the heater 43 and the upper surface of the pressure roller 44 are pressed against each other through the fixing film 41 against the elasticity of the elastic layer, forming a fixing nip portion of a predetermined width as a heating portion.
[0082] The pressure roller 44 is driven to rotate at a predetermined peripheral speed in the counterclockwise direction indicated by the arrow by a driving means (not shown). A rotational force acts on the cylindrical fixing film 41 due to the frictional force of the pressure roller 44 and the fixing film 41 at the fixing nip portion caused by the rotational drive of the pressure roller 44. The fixing film 41 then comes into a driven rotation state in the clockwise direction indicated by the arrow while sliding in close contact with the downward surface of the heater 43. The support member (heater holder) 46 also serves as a rotation guide member for the cylindrical fixing film 41.
[0083] The pressure roller 44 is driven to rotate, and the cylindrical fixing film 41 is driven to rotate accordingly, and the heater 43 is energized, causing the heater to heat up quickly and reach a predetermined temperature, thus being in a temperature-regulated state. In this state, the recording material P carrying the unfixed toner image T is introduced between the fixing film 41 and the pressure roller 44 in the fixing nip portion. Then, in the fixing nip portion, the toner image-carrying side of the recording material P is in close contact with the outer surface of the fixing film 41, and the recording material P is sandwiched and transported together with the fixing film 41 to the fixing nip portion. During this sandwiching and transporting process, the recording material P is heated by the heat of the fixing film 41 heated by the heater 43, and the unfixed toner image T on the recording material P is heated and pressurized onto the recording material P, thereby being melted and fixed. Fixing nip portion T The recording material P that has passed through is separated from the surface of the fixing film 41 by the curvature and is discharged and conveyed.
[0084] Reference numeral 45 denotes a contact thermometer (thermistor) that measures the temperature of the fixing film 41 heated by the heater 43 and passes the detection result to a temperature control means (not shown). Reference numeral 46 denotes a heater holder, which is a member that holds the heater 43 that has been heated to a high temperature.
[0085] Examples of methods for measuring various physical properties in the present disclosure are shown below. <Method of measuring endothermic peak temperature and endothermic amount> First, the surface layer is isolated from the electrophotographic member. Specifically, the surface layer is peeled off from the base layer together with the elastic layer, and the elastic layer bonded to the surface layer is dissolved in a solvent to isolate only the surface layer. The isolated surface layer is cut into a size of about 2 mm x 2 mm so that it fits into the DSC measurement pan.
[0086] The endothermic peak temperature and endothermic amount are measured using a differential scanning calorimeter (product name: Q2000, manufactured by TA Instruments). The melting points of indium and zinc are used for temperature correction of the detector of the device, and the heat of fusion of indium is used for heat correction. Specifically, 4 mg of the surface layer is precisely weighed and placed in an aluminum pan. An empty aluminum pan is used as a reference. The measurement is performed in the measurement range of 25°C to 400°C at a heating rate of 20°C / min. The first measurement is performed by heating to 400°C and holding for 5 minutes, and then cooling to 25°C at a cooling rate of 20°C / min. The second measurement is then performed in the same manner as the first measurement. In the first heating process, the area enclosed by the temperature-endothermic curve including the endothermic peak and the baseline is the endothermic amount. In the second heating process, the temperature at which the maximum endothermic peak occurs on the temperature-endothermic curve in the temperature range of 25°C to 400°C is the endothermic peak temperature.
[0087] <Measuring method for area mean diameter D3 and number mean diameter D1 of spherulites> First, the surface layer is isolated from the electrophotographic member in the same manner as in the measurement of the endothermic peak temperature and endothermic amount. The outer surface of the isolated surface layer is then observed with a microscope (product name: ECLIPSE LV100NDA, manufactured by Nikon Corporation) to obtain an observation image of the spherulites. The observation conditions are switched to transmitted illumination, the analyzer and the transmitted illumination polarizer are crossed at right angles to adjust to cross Nicols, and a 20x objective lens is used. By using a transmitted polarizing microscope, an observation image can be obtained that allows the structure of the spherulites to be confirmed. Next, the contours of 200 spherulites are manually extracted from the obtained observation image of the spherulites. The extraction is performed by extracting the boundary line of each Maltese cross in the observation image as the contour of the spherulite, since each spherulite has a cross-shaped shadow called a Maltese cross. The area of each spherulite is calculated using the image analysis software "ImageJ". The area-average diameter D3 and number-average diameter D1 of the spherulites are calculated from the areas of the 200 spherulites and the circle-equivalent diameter calculated from each area.
[0088] <Method of measuring the arithmetic mean roughness Ra of the outer surface of the surface layer> The arithmetic mean roughness Ra of the outer surface of the surface layer is measured using a contact type roughness meter (product name: SE-3500, manufactured by Kosaka Manufacturing Co., Ltd.) The various conditions for the measurement are as follows. Standards: Japanese Industrial Standards (JIS) B0601:2001 / ISO4287-1997 (roughness) Cutoff wavelength: 0.8 mm Evaluation length: 4.0mm Scanning speed: 1.0mm / s Measurement magnification: 5000x
[0089] <Method of measuring carbon element ratio, fluorine element ratio, and oxygen element ratio on the surface layer facing the elastic layer> First, the surface layer is isolated from the electrophotographic member in the same manner as in the measurement of the endothermic peak temperature and endothermic amount described above.Then, the carbon element ratio C atomic %, fluorine element ratio F atomic %, and oxygen element ratio O atomic % present on the surface of the isolated surface layer facing the elastic layer are measured by ESCA (X-ray photoelectron spectroscopy). The various conditions for the ESCA measurement are as follows: Equipment used: ULVAC-PHI Quantum2000 X-ray photoelectron spectrometer measurement conditions: X-ray source Al Kα X-ray: 100μm 25W 15kV PassEnergy: C 58.70eV F 93.90eV O 58.70 eV The surface element ratio (atomic %) is calculated from the measured peak intensity of each element using the relative sensitivity factor provided by PHI Co., Ltd. The standard for element ratio (atomic %) is the value when the total of carbon, fluorine and oxygen is taken as 100 atomic %.
[0090] <Method for measuring surface layer thickness> First, in the same manner as in the measurement of the endothermic peak temperature and endothermic amount, the surface layer is isolated from the electrophotographic member. Then, the thickness of the isolated surface layer is measured using a micrometer. As the micrometer, for example, a high-precision digital micrometer "MDH-25MB" (product name) manufactured by Mitutoyo Corporation can be used. EXAMPLES
[0091] The present disclosure will be described in more detail below using examples and comparative examples, but the aspects of the present disclosure are not limited thereto.
[0092] The methods for measuring the various physical properties in the present examples are shown below. <Method of measuring endothermic peak temperature and endothermic amount> First, the surface layer was isolated from the electrophotographic member. Specifically, the surface layer was peeled off from the base layer together with the elastic layer, and the elastic layer bonded to the surface layer was immersed in a silicone dissolving agent (e-Solv 21RS (manufactured by Kaneko Chemical Co., Ltd.) and placed in a water tank of an ultrasonic cleaning device (product name: Bransonic (model 2510J-DTH); manufactured by Emerson Japan Co., Ltd.), and ultrasonic waves were applied for 60 minutes to dissolve the elastic layer. From the isolated surface layer, a piece of about 2 mm x 2 mm was cut out so as to fit into the measurement pan of the DSC.
[0093] The endothermic peak temperature and endothermic amount were measured using a differential scanning calorimeter (product name: Q2000, manufactured by TA Instruments). The melting points of indium and zinc were used for temperature correction of the detector of the device, and the heat of fusion of indium was used for heat correction. Specifically, 4 mg of the surface layer was precisely weighed and placed in an aluminum pan. An empty aluminum pan was used as a reference. The measurement was performed at a temperature increase rate of 20°C / min in the measurement range of 25°C to 400°C. The first time, the temperature was increased to 400°C and held for 5 minutes, and then the temperature was decreased to 25°C at a rate of 20°C / min. The second measurement was then performed in the same manner as the first time. In the first heating process, the area enclosed by the temperature-endothermic curve including the endothermic peak and the baseline was taken as the endothermic amount. In the second heating process, the temperature at which the maximum endothermic peak occurred on the temperature-endothermic curve in the temperature range of 25°C to 400°C was taken as the endothermic peak temperature.
[0094] <Measuring method for area mean diameter D3 and number mean diameter D1 of spherulites> First, the surface layer was isolated from the electrophotographic member in the same manner as in the measurement of the endothermic peak temperature and endothermic amount. The outer surface of the isolated surface layer was then observed with a microscope (product name: ECLIPSE LV100NDA, manufactured by Nikon Corporation) to obtain an observation image of the spherulites. The observation conditions were transmission The illumination was switched on, the analyzer and the polarizer for transmitted illumination were aligned perpendicular to each other and adjusted to cross Nicols, and a 20x objective lens was used. Next, the contours of 200 spherulites were manually extracted from the observation images of the obtained spherulites. The extraction was performed by extracting the boundary line of each Maltese cross in the observation image as the contour of the spherulite, since each spherulite has a cross-shaped shadow called a Maltese cross. The area of each spherulite was calculated using the image analysis software "ImageJ". The area-average diameter D3 and number-average diameter D1 of the spherulites were calculated from the areas of the 200 spherulites and the circle-equivalent diameter calculated from each area.
[0095] <Method of measuring the arithmetic mean roughness Ra of the outer surface of the surface layer> The arithmetic mean roughness Ra of the outer surface of the surface layer was measured using a contact type roughness meter (product name: SE-3500, manufactured by Kosaka Manufacturing Co., Ltd.) The various conditions for the measurement are as follows. Standards: Japanese Industrial Standards (JIS) B0601:2001 / ISO4287-1997 (roughness) Cutoff wavelength: 0.8 mm Evaluation length: 4.0mm Scanning speed: 1.0mm / s Measurement magnification: 5000x
[0096] <Method of measuring carbon element ratio, fluorine element ratio, and oxygen element ratio on the surface layer facing the elastic layer> First, the surface layer was isolated from the electrophotographic member in the same manner as in the measurement of the endothermic peak temperature and endothermic amount described above.The carbon element ratio C atomic %, fluorine element ratio F atomic %, and oxygen element ratio O atomic % present on the surface of the isolated surface layer facing the elastic layer were measured by ESCA (X-ray photoelectron spectroscopy). The various conditions for the ESCA measurement are as follows: Equipment used: ULVAC-PHI Quantum2000 X-ray photoelectron spectrometer measurement conditions: X-ray source Al Kα X-ray: 100μm 25W 15kV PassEnergy: C 58.70eV F 93.90eV O 58.70 eV The surface element ratio (atomic %) was calculated from the peak intensity of each element measured using the relative sensitivity factor provided by PHI Co., Ltd. The standard for element ratio (atomic %) is the value when the total of carbon, fluorine and oxygen is taken as 100 atomic %.
[0097] <Method for measuring surface layer thickness> First, the surface layer was isolated from the electrophotographic member in the same manner as in the measurement of the endothermic peak temperature and endothermic amount. Then, the thickness of the isolated surface layer was measured using a micrometer (product name: high-precision digital micrometer MDH-25MB, manufactured by Mitutoyo Corporation).
[0098] <Example 1> In this example, a fixing film as shown in FIG. 3 was prepared.
[0099] (Inner surface treatment of PFA tube) Neoflon PFA: A PFA tube with a thickness of 20 μm obtained by extrusion molding using AP-231SH (manufactured by Daikin Industries, Ltd.) as a raw material was used. An aqueous solution containing 5% by mass of sodium benzoate and 1% by mass of Surflon S-113 (manufactured by AGC Seimi Chemical Co., Ltd.) was applied to the entire inner surface of the PFA tube and allowed to dry naturally. Then, 300 mJ / cm2 The tube was irradiated with six shots of KrF excimer laser light of 1 / 1000 s.p.p. to obtain a PFA tube with a treated inner surface.
[0100] (base layer) The base layer was made of SUS with an inner diameter of 24 mm and a thickness of 30 μm.
[0101] (Formation of inner sliding layer) First, an aromatic tetracarboxylic dianhydride or its derivative and an aromatic diamine in approximately equimolar amounts were reacted in an aprotic polar organic solvent to obtain a polyimide precursor solution. The obtained polyimide precursor solution was applied to the inner circumferential surface of the base layer by a ring coating method, and after drying the solvent in an electric furnace, the resultant was heated at 260 to 400°C for about 1 hour to form an inner sliding layer. The thickness of the inner sliding layer was set to 12 μm.
[0102] (Formation of primer layer and elastic layer) A primer layer and an elastic layer were formed on the base layer on which the inner sliding layer was formed by the following procedure. A hydrosilyl silicone primer (DY39-051 A / B; Dow Toray) was applied onto the base layer and cured by heating for 5 minutes at 200° C. A liquid addition-curing silicone rubber mixture containing the following components (a) to (d) was applied onto the primer layer to a thickness of 250 μm and cured by heating for 30 minutes at 200° C. to form a silicone rubber elastic layer with a thickness of 250 μm.
[0103] (Silicone rubber mixture) Component (a): Linear organopolysiloxane having an unsaturated aliphatic group Component (b): Organopolysiloxane having active hydrogen bonded to silicon Component (c): Catalyst Component (d): Thermally conductive filler
[0104] First, 100 parts by mass of a silicone polymer having vinyl groups, which are unsaturated aliphatic groups, only at both ends of the molecular chain and having methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups, was prepared as component (a). This silicone polymer (trade name: DMS-V35, manufactured by Gelest, viscosity 5000 mm 2 / s) will be referred to as "Vi" from here on. Next, 370 parts by mass of alumina (product name: Amina Beads CB-P10, manufactured by Showa Denko K.K.) was added to this Vi as component (d), and the mixture was placed in a planetary mixer (Thinky Corporation, ARV-5000) and stirred and mixed at 600 rpm for 2 minutes to obtain mixture 1.
[0105] Next, 0.2 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.), which is a cure retarder, was dissolved in the same weight of toluene and added to the mixture 1 to obtain a mixture 2. Next, 0.1 parts by mass of a hydrosilylation catalyst (platinum catalyst: a mixture of 1,3-divinyltetramethyldisiloxane platinum complex, 1,3-divinyltetramethyldisiloxane, and 2-propanol) as component (c) was added to mixture 2 to obtain mixture 3. Furthermore, as component (b), a silicone polymer having a linear siloxane skeleton and having active hydrogen groups bonded to silicon only on the side chain (product name: HMS-301, manufactured by Gelest, viscosity 30 mm 2 1.1 parts by mass of 1.2 parts by mass of 1.2-hexanediaminetetraacetate (hereinafter referred to as "SiH") was weighed out. This was added to mixture 3 and mixed thoroughly to obtain a liquid addition-curing silicone rubber mixture.
[0106] (Applying the adhesive layer) After forming the elastic layer, an adhesive (SE1819CV) is applied to the elastic layer using the ring coating method. A / B (manufactured by Dow Toray) was applied to a thickness of 7 μm.
[0107] (Formation of surface layer) After the adhesive was applied, the PFA tube, which had been subjected to the above-mentioned inner surface treatment as a surface layer, was covered over the adhesive by a method of vacuum expanding and covering from the outside (vacuum expansion covering method). Specifically, the PFA tube was attached under vacuum to the inner surface of an outer cylinder having an inner diameter larger than the outer diameter of the workpiece after the adhesive was applied and the elastic layer was formed, and the PFA tube was expanded in diameter, and the workpiece was inserted into the tube, and then the vacuum was released to cover the adhesive. After removing excess adhesive and air between the PFA tube and the elastic layer with an O-ring or the like, the adhesive was cured and bonded using a heating means such as an electric furnace. Specifically, the workpiece was heated at 200°C for 2 minutes using an electric furnace. Then, both ends were cut to the desired length (336.5 mm).
[0108] (Heat treatment of surface layer) After cutting both ends to the desired length, the piece was inserted into a heating cylinder with an inner diameter of φ42 mm, and the entire area was heat-treated by a band heater inside the heating cylinder. The heating temperature was 330°C, and the heat treatment was performed so that the actual temperature of the surface layer was equal to or higher than the melting temperature of PFA.
[0109] The heating time was set to 3 minutes after the fixing film was placed in the heating cylinder, which was the time required for the surface layer's actual temperature to reach the desired heat treatment temperature. After 3 minutes had passed since the film was placed in the heating cylinder, the heating cylinder was cooled to 200°C at a rate of 20°C / min, and then the film was taken out of the heating cylinder into a room temperature atmosphere to obtain a fixing film. The endothermic peak temperature, endothermic amount, D3, D1, Ra, and CF / 2-O values of the prepared fixing film were determined. These results are shown in Table 1.
[0110] <Evaluation of conformity to paper irregularities (uneven melting)> By observing the melted state of the toner after the toner image formed on the paper is fixed, it is possible to obtain an index of the ability of the fixing member to follow the unevenness of the paper. Using the same film heating fixing device 40 as in the evaluation of wear resistance, 10 sheets of evaluation images for melting unevenness were fixed in succession under an environment of a temperature of 10° C. and a relative humidity of 50%. The paper used was A4 size recycled paper (product name: Recycled Paper GF-R100; manufactured by Canon Inc., thickness 92 μm, basis weight 66 g / m 2The paper used was recycled paper at 70% and Beck smoothness at 23 seconds (measured according to the method of Japanese Industrial Standards (JIS) P8119:1998). The image for evaluating uneven melting was a 10mm x 10mm patch image formed with cyan toner and magenta toner at 100% concentration, and placed near the center of the paper.
[0111] The criteria for uneven melting are as follows: When sufficient heat and pressure are applied to the image area where two colors are formed, the toner melts and the colors mix. In particular, in the concave areas of the paper unevenness, if heat is applied but no pressure is applied, the grain boundaries of the toner remain after fixing, causing uneven melting without sufficient color mixing. If the fixing member cannot conform to the unevenness sufficiently, pressure will be applied to the convex areas and colors will mix, but in the concave areas, color mixing will be insufficient. Therefore, conformability to unevenness was judged by observing the melting state of the image formation area.
[0112] After continuously printing 10 sheets of images for evaluating uneven melting, the 10th sample was taken out and the image forming area was observed under an optical microscope to evaluate uneven melting. The evaluation criteria are as follows. If the evaluation was A to C according to the following evaluation criteria, it was determined that the effects of the present disclosure were obtained. (Evaluation Criteria) A: The toner grain boundaries are completely invisible even in the grooves of the paper fibers, and the colors of both the convex and concave parts are mixed. B: The toner grain boundaries are almost completely invisible even in the grooves of the paper fibers, and the colors of both the convex and concave parts are mixed. C: Although some toner grain boundaries can be observed in the grooves of the paper fibers, the colors of both the convex and concave parts are mostly mixed. D: Only the convex parts of the paper fibers are mixed, and many toner grain boundaries are observed in the concave parts.
[0113] <Abrasion resistance evaluation> The evaluation of the abrasion resistance was carried out using a fixing device 40 of the film heating type shown in Fig. 2, which was assembled with the prepared fixing film. The pressure roller was rotated so that the moving speed (circumferential speed) of the surface of the pressure roller was 320 mm / sec, with the pressure applied to one end being 156.8 N and the total pressure applied being 313.6 N (32 kgf), and the surface temperature of the paper passing portion of the fixing film was controlled to 170°C, and the same size of paper (A4 landscape, GF-C068) was continuously passed through at 70 sheets / min. If the evaluation was A to C according to the following evaluation criteria, it was determined that the effect of the present disclosure was obtained. (Evaluation Criteria) A: Almost no wear on the surface layer is observed even after 500,000 sheets are passed through. B: Almost no wear on the surface layer is observed even after 200,000 sheets are passed, but slight wear on the surface layer due to the edge of the paper is observed after 500,000 sheets are passed. C: After 200,000 sheets are passed, slight wear of the surface layer due to the edge of the paper is observed, and after 500,000 sheets are passed, clear wear of the surface layer due to the edge of the paper is observed. D: After 200,000 sheets are passed, the surface layer is clearly worn away by the edges of the paper.
[0114] <Evaluation of Image Glossiness> The evaluation of the image glossiness was carried out using the fixing device 40 of the film heating type similar to that used in the evaluation of the abrasion resistance. A black solid image was fixed in an environment of 23°C temperature and 50% relative humidity with the surface temperature of the fixing film at the paper passing portion controlled to 160°C. The paper used was A4 size paper (product name: GFC-081 (81.0 g / m 2 ); sold by Canon Marketing Japan Inc.) was used. The 60° gloss of the output image was measured with a gloss meter (a handy gloss meter PG-1M manufactured by Nippon Denshoku Industries Co., Ltd.), and the average value was evaluated according to the following criteria. The 60° gloss is the glossiness measured at an incident angle of 60°. In the case of an incident angle of 60°, the glossiness is a value where the specular reflectance (10%) of light on a glass surface layer having a refractive index of 1.567 over the entire visible wavelength range is taken as 100. If the evaluation was A to C according to the following evaluation criteria, it was determined that the effects of the present disclosure were obtained. (Evaluation Criteria) A: Gross is 10 or more B: Gross is 8 or more but less than 10 C: Gross is 6 or more but less than 8 D: Gross less than 6
[0115] <Example 2> A fixing film was obtained in the same manner as in Example 1, except that the raw material of the PFA tube was changed to Neoflon PFA: AP-230 (manufactured by Daikin Industries, Ltd.).
[0116] <Example 3> A fixing film was obtained in the same manner as in Example 1, except that in the heat treatment of the surface layer, the cooling rate of the heating barrel was changed to 50° C. / min.
[0117] <Example 4> A fixing film was obtained in the same manner as in Example 1, except that in the heat treatment of the surface layer, the cooling rate of the heating barrel was changed to 60° C. / min.
[0118] <Example 5> A fixing film was obtained in the same manner as in Example 1, except that in the treatment of the inner surface of the PFA tube, the number of shots of the KrF excimer laser light was changed to 5 shots.
[0119] <Example 6> A fixing film was obtained in the same manner as in Example 1, except that the raw material of the PFA tube was changed to Neoflon PFA: AP-230 (manufactured by Daikin Industries, Ltd.) and the cooling rate of the heating barrel in the heat treatment of the surface layer was changed to 8°C / min.
[0120] <Example 7> A fixing film was obtained in the same manner as in Example 1, except that the thickness of the PFA tube was changed to 30 μm.
[0121] <Example 8> A fixing film was obtained in the same manner as in Example 1, except that the thickness of the PFA tube was changed to 40 μm.
[0122] <Example 9> A fixing film was obtained in the same manner as in Example 1, except that in the treatment of the inner surface of the PFA tube, the number of shots of the KrF excimer laser light was changed to 10 shots.
[0123] <Comparative Example 1> The raw material of the PFA tube was changed to 451HP-J (manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd.), and the number of shots of KrF excimer laser light in the treatment of the inner surface of the PFA tube was changed to 2. In addition, in the heat treatment of the surface layer, after 3 minutes had elapsed since the fixing film was placed in the heating barrel, the heating barrel was taken out of the heating barrel into a room temperature atmosphere without cooling it, and the fixing film was then naturally cooled to obtain the fixing film. A fixing film was obtained in the same manner as in Example 1 except for the above.
[0124] <Comparative Example 2> The raw material of the PFA tube was changed to P-66P (manufactured by AGC Inc.), and the number of shots of the KrF excimer laser light in the treatment of the inner surface of the PFA tube was changed to 2. In addition, in the heat treatment of the surface layer, after 3 minutes had elapsed since the fixing film was placed in the heating barrel, the heating barrel was removed from the heating barrel into a room temperature atmosphere without cooling it, and allowed to cool naturally. A fixing film was obtained in the same manner as in Example 1 except for the above.
[0125] <Comparative Example 3> A fixing film was obtained in the same manner as in Example 1, except that the raw material of the PFA tube was changed to 959HP Plus (manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd.) and the number of shots of KrF excimer laser light in the inner surface treatment of the PFA tube was changed to two shots.
[0126] <Comparative Example 4> In the treatment of the inner surface of the PFA tube, the number of shots of the KrF excimer laser light was changed to 2. In addition, in the heat treatment of the surface layer, after 3 minutes had elapsed since the fixing film was placed in the heating barrel, the heating barrel was removed from the heating barrel into a room temperature atmosphere without cooling it, and then naturally cooled. A fixing film was obtained in the same manner as in Example 1 except for the above.
[0127] <Comparative Example 5> A fixing film was obtained in the same manner as in Example 1, except that in the treatment of the inner surface of the PFA tube, the number of shots of the KrF excimer laser light was changed to two shots.
[0128] In Examples 2 to 9 and Comparative Examples 1 to 5, the endothermic peak temperature, endothermic amount, D3, D1, Ra, and CF / 2-O values of the fixing films prepared were obtained. In addition, evaluation of abrasion resistance, evaluation of melting unevenness, and evaluation of image gloss were performed based on the same evaluation method as in Example 1. The results are shown in Table 1.
[0129] [Table 1] In the table, the endothermic peak temperature indicates the endothermic peak temperature in the second heating process by DSC, and the endothermic amount indicates the amount of endothermic heat in the first heating process.
[0130] The present disclosure relates to the following configurations. (Configuration 1) 1. An electrophotographic member having at least a base layer, an elastic layer, and a surface layer, in that order, the surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, The sample sampled from the surface layer was used as a measurement sample, and measurements were carried out twice using a differential scanning calorimeter (DSC) at a heating rate and a cooling rate of 20° C. / min. The endothermic curves obtained were as follows: The endothermic peak temperature in the second heating process is 304°C or less, The amount of heat absorbed during the first heating process is 21 J / g or more, An electrophotographic member, wherein D3 is an area average diameter of the spherulites on the outer surface of the surface layer, and D3 is 40 μm or less. (Configuration 2) 2. The electrophotographic member according to claim 1, wherein the surface layer has an outer surface having an arithmetic mean roughness Ra of 0.20 μm or less. (Configuration 3) 3. The electrophotographic member according to configuration 1 or 2, wherein D3 / D1 is 1.5 or less, where D1 is the number-average diameter of the spherulites on the outer surface of the surface layer. (Configuration 4) 4. The electrophotographic member according to any one of configurations 1 to 3, wherein D3 is 5 μm or more. (Configuration 5) 5. The electrophotographic member according to any one of Configurations 1 to 4, wherein the amount of heat absorbed during the first temperature increase process is 27 J / g or less. (Configuration 6) 6. The electrophotographic member according to any one of Configurations 1 to 5, wherein the endothermic peak temperature in the second temperature-raising process is 297° C. or higher. (Configuration 7) The endothermic peak temperature in the second heating process is 300° C. or higher. 2. The electrophotographic member according to claim 1 . (Configuration 8) When the carbon element ratio of the surface layer on the side facing the elastic layer is C atomic %, the fluorine element ratio is F atomic %, and the oxygen element ratio is O atomic %, CF / 2-O≧30 8. The electrophotographic member according to any one of Configurations 1 to 7, which satisfies the above. (Configuration 9) 9. The electrophotographic member according to any one of configurations 1 to 8, wherein the surface layer has a thickness of 30 μm or less. (Configuration 10) The electrophotographic member according to any one of configurations 1 to 9, wherein the surface layer has a thickness of 0 to 30 μm. (Configuration 11) 11. The electrophotographic member according to any one of configurations 1 to 10, wherein the electrophotographic member is an electrophotographic belt having an endless shape. (Configuration 12) 12. The electrophotographic member of embodiment 11, wherein the electrophotographic member is a fuser belt. (Configuration 13) A fixing device in an electrophotographic image forming apparatus, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 13. A fixing device, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of Configurations 1 to 12. (Configuration 14) An electrophotographic image forming apparatus including a fixing device, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 13. An electrophotographic image forming apparatus, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of Configurations 1 to 12. [Explanation of symbols]
[0131] 10: image forming unit, 11: photosensitive drum, 12: charger, 13: laser scanner, 14: developer, 15: cleaner, 17: primary transfer blade, 20: paper feed cassette, 25: multi-paper feed tray, 23: registration roller pair, 31: intermediate transfer belt, 35: secondary transfer roller, 40: fixing unit, 41: fixing film, 41a: surface layer, 41b: base layer, 41c: elastic layer, 43: heating element, 44: pressure roller, 45: contact type thermistor, 46: heater holder, P: recording material, T: toner
Claims
1. 1. An electrophotographic member having at least a base layer, an elastic layer, and a surface layer, in that order, the surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, A sample taken from the surface layer was used as a measurement sample, and measurements were carried out twice using a differential scanning calorimeter (DSC) at a heating rate and a cooling rate of 20° C. / min. In the endothermic curve, The endothermic peak temperature in the second heating process is 304° C. or less; The amount of heat absorbed during the first heating process is 21 J / g or more; An electrophotographic member, wherein D3 is an area average diameter of spherulites on the outer surface of said surface layer, and D3 is 40 μm or less.
2. 2. The electrophotographic member of claim 1, wherein the arithmetic mean roughness Ra of the outer surface of said surface layer is 0.20 [mu]m or less.
3. 2. The electrophotographic member of claim 1, wherein, when D1 is a number average diameter of said spherulites on the outer surface of said surface layer, D3 / D1 is 1.5 or less.
4. 2. The electrophotographic member of claim 1 wherein said D3 is 5 [mu]m or greater.
5. 2. The electrophotographic member according to claim 1, wherein the amount of heat absorbed during the first temperature rise process is 27 J / g or less.
6. 2. The electrophotographic member according to claim 1, wherein the endothermic peak temperature in the second temperature increase process is 297[deg.] C. or higher.
7. 2. The electrophotographic member according to claim 1, wherein the endothermic peak temperature in the second temperature increase process is 300[deg.] C. or higher.
8. When the carbon element ratio of the surface layer facing the elastic layer is C atomic %, the fluorine element ratio is F atomic %, and the oxygen element ratio is O atomic %, C-F / 2-O≧30 2. The electrophotographic member of claim 1, wherein
9. 2. An electrophotographic member according to claim 1, wherein said surface layer has a thickness of 30 microns or less.
10. 2. The electrophotographic member of claim 1, wherein the surface layer has a thickness of from 10 to 30 μm.
11. 2. The electrophotographic member of claim 1 wherein said electrophotographic member is an electrophotographic belt having an endless configuration.
12. 12. The electrophotographic member of claim 11, wherein said electrophotographic member is a fuser belt.
13. A fixing device in an electrophotographic image forming apparatus, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, A fixing device, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of claims 1 to 12.
14. An electrophotographic image forming apparatus including a fixing device, The fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 13. An electrophotographic image forming apparatus, wherein at least one of said fixing member and said pressure member is the electrophotographic member according to any one of claims 1 to 12.
Citation Information
Patent Citations
Film for fixing part
JP2000010430A
Fixing roll and method for manufacturing the same
JP2007093650A